Post-humanist artistic research by production of performance and Techno-Lab workshops in Sapmi - Griniuk, Marija (Frontiers in Communication, 2024)
We are living in times of data-driven selves and data-defined artistic personas, an age in which the action of border-crossing has become a normative within an artistic work and an artist's life. We might cross the physical borders or the borders of our normatives. Each case of border-crossing awakens our awareness. The question of how an artwork is made is now as sharp as ever before. Contemporary technologies involving AI are opening a wide spectrum of possibilities for enhancing creativity and sustainability within the creation of performance artworks, which is traditionally seen as an individual process of a human creator. The main research question within this study is as follows: How can performance and workshop creation through collaboration between humans and AI and humans and technology be understood as post-humanist artistic research? The sub-question is: How is such a creation process different from artistic creation using traditional tools associated with artistic work? These questions are answered by investigating a case of Techno-Lab in Sapmi and a performance artwork creation process through the method of post-humanist artistic research. The key findings outline the main differences of post-humanist vs. anthropocentric artistic research and art production. The findings can be used to change the current normatives and enhance the radical transcorporeality through interconnections between humans and non-humans—in particular, technology and AI. The findings are relevant to art education and artistic practice representatives.